The Ecological Model of Visual Artists in the Malaysian Contemporary Visual Arts Industry: A Framework Proposal - Syed Abu Bakar, Syed Alwi; Tahir, Azian; Ramli, Ishak (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2018)
The increasingly challenging and competitive artwork production environment has prompted visual artists to have an arrangement of state-of-the-art art production practices. Currently, the system of production and marketing of works does not have a clear guideline in the industry that can help in the survival of professional visual artists in Malaysia. Therefore, this study is designed to get clear feedback from those who are already active in this industry related to the challenges faced and the marketability of the works of visual artists to continue to compete in the local and international art production stage. This paper aims to identify the non -technical practices required for the successful implementation and marketing of works of art in Malaysia. The results of this study will provide a detailed study of the practices of visual artists in the implementation and marketing that need to be considered by those who will venture into the arena of professional production. Through this paper, a framework has been developed through a comprehensive review from the point of view of literature as well as practical practice. Keywords: Non -technical practice, production of works, visual artists, visuals, art work.